2008
DOI: 10.1109/led.2008.2000966
|View full text |Cite
|
Sign up to set email alerts
|

Self-Heating-Induced Spatial Spread of Interface State Generation by Hot-Electron Effect: Role of the High-Energy Tail Electron

Abstract: The spatial spread of interface states generated by hot-electron effect in the nMOSFET is shown to be significantly increased by self-heating. Substantial generation of interface states in the channel region of the wide-channel strained-Si/SiGe nMOSFET, which suffers from significant self-heating, is observed at a very short stress time. The initial spread of the interface damage is significantly reduced in the narrow-channel strained-Si device, which exhibits a much lesser degree of self-heating. Evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This behavior is similar to the phenomenon of reinforced device degradation by self-heating in silicon on insulating ͑SOI͒ and strained-Si devices. 14,15 It was also observed that the number of electrons in the high-energy tail and the spread of the interface damage into the channel were increased by self-heating in strained-Si devices. 15 Figure 1͑d͒ shows the spatial distribution of N it induced by HCS at an elevated temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is similar to the phenomenon of reinforced device degradation by self-heating in silicon on insulating ͑SOI͒ and strained-Si devices. 14,15 It was also observed that the number of electrons in the high-energy tail and the spread of the interface damage into the channel were increased by self-heating in strained-Si devices. 15 Figure 1͑d͒ shows the spatial distribution of N it induced by HCS at an elevated temperature.…”
mentioning
confidence: 99%
“…14,15 It was also observed that the number of electrons in the high-energy tail and the spread of the interface damage into the channel were increased by self-heating in strained-Si devices. 15 Figure 1͑d͒ shows the spatial distribution of N it induced by HCS at an elevated temperature. Compared with the results at room temperature, the distribution of generated N it at the elevated temperature spreads more into the channel.…”
mentioning
confidence: 99%
“…This situation leads to high electric fields typical for modern MOSFETs, accelerating carriers up to relatively high energies and thereby enhancing the detrimental phenomenon of hot-carrier degradation (HCD), which was labeled as the most severe reliability issue in such FETs [1][2][3]. The introduction of three-dimensional transistor structures such as fin and nanowire (NW) FETs gives rise to another reliability issue called "self-heating" (SH) [4][5][6][7]. Indeed, in these confined architectures a narrow semiconductor channel is surrounded by a dielectric layer with a low thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%